2021
DOI: 10.1021/acsomega.1c01007
|View full text |Cite
|
Sign up to set email alerts
|

4-Fluoro-Threonine: From Diastereoselective Synthesis to pH-Dependent Conformational Equilibrium in Aqueous Solution

Abstract: 4-Fluoro-threonine, the only fluoro amino acid of natural origin discovered so far, is an interesting target for both synthetic and theoretical investigations. In this work, we lay the foundation for spectroscopic characterization of 4-fluoro-threonine. First, we report a diastereoselective synthetic route, which is suitable to produce synthetic material for experimental characterization. The addition of the commercially available ethyl isocyanoacetate to benzyloxyacetaldehyde led to the corresponding benzylox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…Final deprotection to ( 28 ) was achieved via treatment with 6N HCl [ 116 ]. Potenti et al recently reported another synthetic route avoiding the use of Ru(III) [ 117 ]. The preparation of 4-chloro-lysine ( 29 ) has been reported by reacting commercially available lysine hydrochloride with Cl 2 under irradiation with UV light.…”
Section: Halo-amino Acids and Halogenated Non-ribosomal Peptidesmentioning
confidence: 99%
“…Final deprotection to ( 28 ) was achieved via treatment with 6N HCl [ 116 ]. Potenti et al recently reported another synthetic route avoiding the use of Ru(III) [ 117 ]. The preparation of 4-chloro-lysine ( 29 ) has been reported by reacting commercially available lysine hydrochloride with Cl 2 under irradiation with UV light.…”
Section: Halo-amino Acids and Halogenated Non-ribosomal Peptidesmentioning
confidence: 99%
“…Therefore, we resorted to a purposely tailored version of the Island Model Evolutionary Algorithm (IMEA [14,27] ), which has proven to be an extremely effective machine-learning algorithm for the structural characterization of several flexible molecules. [10,27] The exploration step employed the GFN2-xTB semi empirical method [13] and led to, in addition to the 21 structures deriving from fluorination of Thr, several additional conformers. This panel of structures, together with all missing staggered conformers with respect to the χ 3 dihedral for each candidate (see Table S2 and Figure S1 of the Supplementary Information, SI), was selected for further refinement.…”
Section: Conformational Landscapementioning
confidence: 99%
“…[45,46] To probe the a priori description of the conformational landscape of 4FT, a sufficient amount of the racemic diastereoisomer (rac-1; see the inset of Figure 1) was obtained following the recently published route (with further details being given in the SI). [10] Being 4FT a solid compound with a high melting point (182-183 °C), [47] the laser ablation (LA) technique [26] was then employed in combination with a chirped-pulse Fourier-transform Microwave spectrometer (CP-FTMW; details are provided in the SI) [48,49] to record the rotational spectrum of 4FT in the 6.0-14.0 GHz frequency region. In the spectrometer, the gas-phase sample is subjected to supersonic expansion.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we are concerned with the use of metaheuristics in the exploration of the Potential Energy Surfaces (PESs) of flexible molecular systems of medium size (roughly containing less than 100 atoms). In previous contributions [15][16][17] we have proposed and validated the application of one of such algorithms, namely the (λ + µ) Island Model Evolutionary Algorithm (IM-EA hereafter), to the investigation of the conformational landscape of biomolecule building blocks 18 or relatively simple organometallic systems 19 . The present contribu-tion presents a number of relevant improvements to the IM-EA method: (i) in the previous contribution we simply checked the capabilities of the method in exploring PESs of flexible systems with the goal of completeness without an in depth discussion of the importance of various components in the method, which is presented in this manuscript; (ii) we previously limited the exploration to dihedral angles of isolated flexible systems, whereas here we present also a new set of operators based on quaternions 20,21 able to deal with inter-molecular interactions; (iii) we add a number of improvements to the method, with new mutation operators and the Hall of Fame mechanism (see section 2.1) and (iv) introduce effective unsupervised clustering of candidate structures in order to reduce as much as possible the number of expensive quantum chemical (QC) computations; neither the computer code, nor the case studies discussed below were presented before.…”
Section: Introductionmentioning
confidence: 99%